What Counts as a Memory? Definitions, Hypotheses, and "Kinding in Progress". Issue 1 (January 2022) - Colaço, David
Abstract: This paper accounts for broad definitions of memory, which extend to paradigmatic memory phenomena, like episodic memory in humans, and phenomena in worms and sea snails. These definitions may seem too broad, suggesting that they extend to phenomena that don't count as memory or illustrate that memory is not a natural kind. However, these responses fail to consider a definition as a hypothesis . As opposed to construing definitions as expressing memory's properties, a definition as a hypothesis is the basis to test inferences about phenomena. A definition as a hypothesis is valuable when the "kinding" of phenomena is ongoing.